Engineering of gold nanorods as multifunctional theranostic agent for photothermal-enhanced radiotherapy of cancer - Lina Xie; Xia Ying; Xinyue Li; Xinyue Tan; Tianzi Zhang; Xujia Zhang; Wen Cai; Feifei An; Xiaoli Liu; Suxia Han (Materials & Design, 2023)
Radiotherapy (RT) is an important method in cancer treatment. Devising conveniently synthesizable and smart multifunctional radiosensitizers is of tremendous significance to improve the cure rate of RT. Gold nanorods (GNRs), which exhibit high X-ray absorption capacity and near-infrared (NIR) photothermal conversion effectiveness, could be utilized as radiosensitizers. In the present study, an all-in-one theranostic nanoagent for photothermal-enhanced RT of cancer was devised based on engineered GNRs with aggregation-induced emission (AIE) attributes. This nanoagent-mediated photothermal therapy (PTT) in combination with RT (PTT-RT) demonstrated excellent photothermal-enhanced RT effect by significantly inhibiting migration and invasion, increasing reactive oxygen species (ROS) production and causing more DNA damage in two different pathological types of cell lines of cervical cancer, compared with mere RT. The PTT-RT based on this nanoagent further showed enhanced RT effect in vivo, and increased the production of some metabolites remarkablely enriched in the phenylalanine metabolism pathway revealed by the metabolomics analysis, compared with RT alone. Meanwhile, this nanoagent exhibited excellent computed tomography imaging (CTI)/photoacoustic imaging (PAI)/fluorescence imaging (FLI)/photothermal imaging (PTI) multi-modal imaging capability. The present research provides a multifunctional platform for optimizing the efficacy of RT and enriches the mechanism study for GNRs-mediated photothermal-enhanced RT.